Effect of Lactiplantibacillus plantarum inoculated on the quality of bran vinegar during the alcohol fermentation stage - JIANG Wenyi, LI Li, LIU Genqiao, FENG Zhiping, LIU Jun (Zhongguo niangzao)
By measuring the CO2 mass loss during the alcohol fermentation stage of bran vinegar, the alcohol content, reducing sugar, total acid content, volatile aroma substances, and sensory quality of the fermented liquor samples, the effects of Saccharomyces cerevisiae and Lactiplantibacillus plantarum inoculated at different time (numbered as S4L, S2L, SL, L2S, L4S, S) on the quality of bran vinegar during the alcohol fermentation stage were studied. The results showed that the CO2 mass loss of the sample was the largest on the first day of fermentation, and then decreased slowly and tended to be stable. The earlier the inoculation time of L. plantarum, the smaller the CO2 mass loss. The inoculation of L. plantarum inhibited the formation of alcohol, and the alcohol content of the samples except for the S4L group was significantly lower (P<0.05), but there was no significant difference among the groups (P>0.05). The total acid content increased gradually with the advance of inoculation time of L. plantarum. The inoculation of L. plantarum significantly improved the utilization rate of reducing sugar in the fermentation system (P<0.05). The main volatile flavor components in fermented liquor samples were esters, alcohols and acids. The inoculation of L. plantarum affected the flavor of the fermented liquor samples, and the earlier the inoculation time of L. plantarum, the higher the total content of esters and alcohols, the more prominent the fruit, grass and sour aroma of liquor sample, but it had a certain inhibitory effect on sweet and grain aroma. Except for L2S group, the content of acetic acid increased with the advance of inoculation time of L. plantarum. In conclusion, the inoculation of L. plantarum could improve the quality of bran vinegar during the alcohol fermentation stage.